The Nylon Pirates - Nicholas Monsarrat (Suffolk Pan Books, 1963)
Alcestis, a British luxury liner, moored in New York and bound on a cruise to the Caribbean, South America and Africa, awaits her exclusive passengers -- businessmen with mid-life crises, large bank balances and unforgiving wives; legacy-laden women looking for love and adventure; and divorcees with settlements to squander. But another group of passengers threatens to upset their opulent trip. These are the twentieth-century pirates -- suave, elegant, discreet and utterly unscrupulous, with a singular purpose in mind and a collection of ruthless strategies.
Keywords: Fiction